2000
DOI: 10.1046/j.1365-313x.2000.00734.x
|View full text |Cite
|
Sign up to set email alerts
|

Diverse effects of overexpression of LEAFY and PTLF, a poplar (Populus) homolog of LEAFY/FLORICAULA, in transgenic poplar and Arabidopsis

Abstract: SummaryPTLF, the Populus trichocarpa homolog of LEAFY (LFY) and FLORICAULA, was cloned to assess its function in a dioecious tree species. In situ hybridization studies showed that the gene was expressed most strongly in developing in¯orescences. Expression was also seen in leaf primordia and very young leaves, most notably in apical vegetative buds near in¯orescences, but also in seedlings. Although ectopic expression of the PTLF cDNA in Arabidopsis accelerated¯owering, only one of the many tested transgenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
134
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(146 citation statements)
references
References 32 publications
12
134
0
Order By: Relevance
“…4). Early onset of flowering in transgenic plants is in concordance with the earlier reports of Leafy overexpression in different species tobacco Nilsson 1995), aspen (Wiegel andNilsson 1995), rice (He et al 2000), poplar (Rottmann et al 2000), citrus (Pena et al 2001) and B. juncea (Roy et al 2009). The PCR positive lines also showed different morphological defects.…”
Section: Phenotypic Analysissupporting
confidence: 89%
See 1 more Smart Citation
“…4). Early onset of flowering in transgenic plants is in concordance with the earlier reports of Leafy overexpression in different species tobacco Nilsson 1995), aspen (Wiegel andNilsson 1995), rice (He et al 2000), poplar (Rottmann et al 2000), citrus (Pena et al 2001) and B. juncea (Roy et al 2009). The PCR positive lines also showed different morphological defects.…”
Section: Phenotypic Analysissupporting
confidence: 89%
“…Gray ex Hook.) (Rottmann et al 2000), and Citrus (Pena et al 2001). This ability of LFY to accelerate flowering is tapped in this study to develop early flowering transgenics of Brassica by overexpression of AtLFY.…”
Section: Introductionmentioning
confidence: 99%
“…Regions of exon 3 in LFY also showed greater than expected latitudinal differentiation. Multiple functional studies have shown that LFY affects flowering and other developmental phenotypes, including in Populus (Rottman et al 2000). In contrast to the very high levels of segregating variation in Populus LFY, Arabidopsis LFY harbors low diversity consistent with a recent selective sweep .…”
Section: Molecular Adaptation Of Phenology Network Genesmentioning
confidence: 99%
“…), as in other species, the rapid development of large leaves is an important determinant of productivity (Ridge et al, 1986; Barigah et al, 1994). In addition, Populus is very quickly becoming recognized as the "model" forest tree, equivalent to Arabidopsis (Taylor, 2002), because it is one of a few woody species where transformation is routine (Rottmann et al, 2000), where a large genomic initiative with several thousand expressed sequence tags is already developed (Sterky et al, 1998), and where the complete physical sequence of the genome will be completed within the next 2 years, as described by Wullschleger et al (2002).1 This work was supported by the EC through its Environment R and D program within the Fourth Framework as research contract ENV4 -CT97-0657 (POPFACE) coordinated by the University of Viterbo and by Natural Environment Research Council and Department of Environment, Food and Rural Affairs (grant nos. GR9/04077 and NFO410 to GT).…”
mentioning
confidence: 99%